Does Living in a Higher Proportion Minority Facility Improve Quality of Life for Racial/Ethnic Minority Residents in Nursing Homes?. Issue 3 (5th June 2020) - Shippee, Tetyana P; Ng, Weiwen; Bowblis, John R
Abstract: Background and Objectives: The proportion of racial/ethnic minority older adults in nursing homes (NHs) has increased dramatically and will surpass the proportion of white adults by 2030.Yet, little is known about minority groups' experiences related to the quality of life (QOL). QOL is a person-centered measure, capturing multiple aspects of well-being. NH quality has been commonly measured using clinical care indicators, but there is growing recognition for the need to include QOL. This study examines the role of individual race/ethnicity, facility racial/ethnic composition, and the interaction of both for NH resident QOL. Research Design and Methods: We used a unique state-level data set that includes self-reported QOL surveys with a random sample of long-stay Minnesota NH residents, using a multidimensional measure of QOL. These surveys were linked to resident clinical data from the Minimum Dataset 3.0 and facility-level characteristics. Minnesota is one of the two states in the nation that collects validated QOL measures, linked to data on resident and detailed facility characteristics. We used mixed-effects models, with random intercepts to model summary QOL score and individual domains. Results: We identified significant racial disparities in NH resident QOL. Minority residents report significantly lower QOL scores than white residents, and NHs with higher proportion minority residents have significantly lower QOL scores. Minority residents have significantly lower adjusted QOL than white residents, whether they are in low- or high-minority facilities, indicating a remaining gap in individual care needs. Discussion and Implications: The findings highlight system-level racial disparities in NH residents QOL, with residents who live in high-proportion minority NHs facing the greatest threats to their QOL. Efforts need to focus on reducing racial/ethnic disparities in QOL, including potential public reporting (similar to quality of care) and resources and attention to provision of culturally sensitive care in NHs to address residents' unique needs.